Commentary or Perspective: Opportunities to Leverage the Use of Global Public Health Innovative Research Technology in Combatting Cybercrime - Mierzwa, Stan; Spath-Caviglia, Lauren; Christov, Iassen (Journal of Leadership, Accountability and Ethics, 2021)
Recently while near my hometown baseball field, I was reminded of the Little League Pledge. Players traditionally recited the pledge prior to the start of a baseball or softball game; two lines particularly stood out to me, they were “I will play fair and strive to win. But, win or lose, I will always do my best.” The first line mentioned got us thinking about the pandemic and rise in cybercrime. Why are there persons willing to partake in cybercrime, taking advantage of the situation the pandemic has created, and not playing fair? Can cybersecurity researchers utilize similar efforts or strategies used by the global public health to combat cybercrimes, during difficult causal situations? This paper will outline a subset of current research taking place concerning cybercrime and COVID-19 through a rapid literature review, bring to light strategies and technologies that can be used to complement the research, and bring a call to action for researchers and practitioners to give this topic greater attention, awareness, and more knowledge and focus.